Sports as an Instrument of Development and National Cohesion: The Nigerian Experience: Array - Efebeh, Vincent Eseoghene (Journal of Danubian Studies and Research, 2020)
Sports is globally regarded as having the ability to foster friendship and peaceful coexistence among peoples across such different barriers as skin colours, country of origin, religion, gender as well as social strata. Sport is a strong source of harnessing diversities that may exist in a political system for sustainable socio-economic and political development. Sports have been used by different countries as justifiable mechanism for foreign policy and a veritable vehicle for peaceful co-existence. However, just as sport is capable of promoting friendship, it can also be used as an instrument of development in same way as it can foster national cohesion especially in plural and heterogeneous societies. To that extent, this paper sets to establish the extent to which sports can be used to engender development. It relied on the qualitative method of gauging information to establish its case. The study reveals that, indeed sports has the potentials of promoting national cohesion in a clime that is fragmented along many divisive lines such as ethnicity, religion, language and many other centrifugal forces; it further reveal that sports can also engender development in all facets such that is will enhance the standard of living of the people. The paper suggests among other things that, there is the need for the government to synergize with the private sector in order for the people and the society at large to reap the benefits that lays in sports and in the sport industry.